2015
DOI: 10.1039/c5tx00001g
|View full text |Cite
|
Sign up to set email alerts
|

Two generation reproduction and teratogenicity studies of feeding diaveridine in Wistar rats

Abstract: Diaveridine (DVD), belonging to the class of compounds called diaminopyrimidines, has been widely used as a bacteriostatic agent. To evaluate the reproductive toxicity and teratogenic potential of DVD, different concentrations of DVD were administered to Wistar rats by feeding diets containing 0, 23, 230, 1150 and 2000 mg kg −1 of DVD. Each group consisting of 18 males and 25 females (F 0 ) was treated with different concentrations of DVD through a 13-week period prior to mating, during mating, gestation, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The kidneys and liver showed the highest concentrations of radioactivity during the sample collection time, implying that these are the key organs for toxicology concerns. Significant toxic effects on the kidneys and liver were confirmed by observing fibroblasts in the kidneys and inflammation in the liver in toxicological studies . The rapid elimination of DVD-related metabolites in swine compared to that in chickens and rats may be related to its extensive metabolism to form polar compounds which promote drug clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The kidneys and liver showed the highest concentrations of radioactivity during the sample collection time, implying that these are the key organs for toxicology concerns. Significant toxic effects on the kidneys and liver were confirmed by observing fibroblasts in the kidneys and inflammation in the liver in toxicological studies . The rapid elimination of DVD-related metabolites in swine compared to that in chickens and rats may be related to its extensive metabolism to form polar compounds which promote drug clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Significant toxic effects on the kidneys and liver were confirmed by observing fibroblasts in the kidneys and inflammation in the liver in toxicological studies. 12 The rapid elimination of DVD-related metabolites in swine compared to that in chickens and rats may be related to its extensive metabolism to form polar compounds which promote drug clearance. Our research showed that the DVD-related residues in the kidneys were eliminated more slowly than those in the liver and other tissues/organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation